Tocilizumab (TCZ) Decreases Angiogenesis in Rheumatoid Arthritis Through Its Regulatory Effect on miR-146a-5p and EMMPRIN/CD147 - Zisman, Devy; Safieh, Mirna; Simanovich, Elina; Feld, Joy; Kinarty, Amalia; Zisman, Liron; Gazitt, Tal; Haddad, Amir; Elias, Muna; Rosner, Itzhak; Kaly, Lisa; Rahat, Michal A. (Frontiers in Immunology, 2021)
Background: Angiogenesis is an important contributor to the development of Rheumatoid arthritis (RA). Tocilizumab (TCZ), an anti-IL-6 receptor antibody, is used in the treatment of RA patients, and has been shown to exert anti-inflammatory effects. However, its effects on angiogenesis are not fully elucidated, and the molecular mechanisms regulating this effect are unknown. Methods: We evaluated the concentrations of several pro- and anti-angiogenic factors and the expression levels of several microRNA molecules that are associated with RA and angiogenesis in serum samples obtained from 40 RA patients, before and 4 months after the initiation of TCZ treatment. Additionally, we used an in vitro co-culture system of fibroblasts (the HT1080 cell line) and monocytes (the U937 cell line) to explore the mechanisms of TCZ action. Results: Serum samples from RA patients treated with TCZ exhibited reduced levels of EMMPRIN/CD147, enhanced expression of miR-146a-5p and miR-150-5p, and reduced angiogenesis as was manifested by the reduced number of tube-like structures formed by EaHy926 endothelial cell line. In vitro, the accumulation of the pro-angiogenic factors EMMRPIN, VEGF and MMP-9 in the supernatants was increased by co-culturing the HT1080 fibroblasts and the U937 monocytes, while the accumulation of the anti-angiogenic factor thrombospondin-1 (Tsp-1) and the expression levels of miR-146a-5p were reduced. Transfection of HT1080 cells with the miR-146a-5p mimic decreased the accumulation of EMMPRIN, VEGF and MMP-9. When EMMPRIN was neutralized with a blocking antibody, supernatants derived from these co-cultures exhibited reduced migration, proliferation and tube formation in functional assays. Conclusions: Our findings implicate miR-146a-5p in the regulation of EMMPRIN and propose that TCZ affects angiogenesis through its effects on EMMRPIN and miR-146a-5p.